Current Status of Solar Energy in India: An Overview” - Ranjan, Aashish; Purohit, Jyoti; waroop, Rams (IJRDO - Journal of Electrical And Electronics Engineering, 2017)
India is a fast growing country having more than one billion people. It is the third largestcommercial energy consumer in the world after China and the United States. The commercialsources are usually fossil fuels like: coal and petroleum. These are available in limited amount.The over consumption of fossil fuels can lead to energy crisis and serious environmental issuessuch as: Ozone depletion, global warming and acid rain. The future of renewable energy sources is bright because it is abundant, inexhaustible, pollution free and universal sources of energy. The sun is an enormous source of energy on the earth. So, it will play an important role to solve the energy crisis of India because it is situated in the equatorial sun belt of the earth. With about300 clear and sunny days in a year, India receives abundant radiation energy from the sun.